The Indigenization of the Meaning of Poor and Poor in Qur'an - Hamzah, Muhammad Yasser; Mursalim, Mursalim; Izzuddin, Washif (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This article examines the meaning of needy and poor in the Qur'an and its implementation in the social context in Indonesia through an indigenization approach. By using literature review methods and descriptive analysis, this research reveals the meaning of needy and poor from the perspective of contemporary language, terms and interpretations. The concept of Islamic indigenization initiated by KH. Abdurrahman Wahid (Gus Dur) became the theoretical basis for adapting universal Islamic values ​​to the Indonesian context. The research results show that the needy and the poor have fundamental differences, where the poor reflect a more severe condition of deprivation than the poor. The implementation of this concept in public policy in Indonesia, such as poverty criteria by BPS and zakat regulations by BAZNAS, shows the relevance of Islamic values ​​in dealing with poverty. This research also highlights differences in poverty indicators in various regions in Indonesia which are influenced by local social and economic conditions. This research recommends updating poverty data and indicators to adapt to socio-economic dynamics, as well as the need for a contextual approach in implementing policies based on Islamic values ​​to ensure more inclusive social justice. Keywords: Indigenousization, Islam, Poverty, Had Kifayah.